Labor market issues in Japan and Germany - Schober, Franz; Matsugi, Takashi, 1936- (Schriften zu Regional- und Verkehrsproblemen in Industrie- und Entwicklungsländern, 1998)
This publication deals with current labor market issues in Japan, Germany and the European Union. In the book, the ""labor market"" serves as central focus point, yet the methodology of addressing this focus point is very broad. It includes the analysis of the general labor market development and its conditions in the European Union and in Japan as well as more specific investigations, such as the impact of fiscal policies, exchange rates or information technology on the demand for labor.